PROBLEMS OF FINANCIAL REPORTING IN THE DIGITAL ECONOMY - Yunusova Gavxar Ibadulla qizi (Modern American Journals, 2025)
Financial reporting should be simple and understandable, adapted for its users. Economic literature often emphasizes the necessity of using foreign accounting standards to regulate the accounting system. However, such views are not entirely applicable to our regional specificities, as a certain accounting system has already been established in our Republic.